The Value of Protocol Biopsies to Identify Patients With De Novo Donor‐Specific Antibody at High Risk for Allograft Loss. Issue 6 (25th January 2017) - Schinstock, C. A.; Cosio, F.; Cheungpasitporn, W.; Dadhania, D. M.; Everly, M. J.; Samaniego‐Picota, M. D.; Cornell, L.; Stegall, M. D.
Abstract : De novo donor‐specific antibody (dnDSA) is associated with antibody‐mediated rejection (AMR) and allograft loss, yet the allograft histology associated with dnDSA remains unclear. The aim of this study was to examine the allograft histology associated with dnDSA in patients with serial surveillance biopsies. We retrospectively studied adult conventional solitary kidney transplant recipients from October 2007 to May 2014. The definition of dnDSA was new donor‐specific antibody (DSA) with mean fluorescence intensity (MFI) >1000. The incidence of dnDSA was 7.0% (54 of 771) over mean follow‐up of 4.2 ± 1.9 years. Patients with dnDSA had reduced death‐censored allograft survival (87.0% vs. 97.0% no dnDSA, p < 0.01). Moreover, 94% of patients received a biopsy after dnDSA (mean of three biopsies per patient). AMR was present in 25.0% and 52.9% of patients at dnDSA detection and at 1 year, respectively. Patients with both class I and II dnDSA had the highest rate of allograft loss. The higher the sum MFI at dnDSA detection, the higher the incidence of AMR. In conclusion, patients with dnDSA without AMR at time of detection may benefit from a follow‐up biopsy within 1 year because AMR can be missed initially. In addition, the dnDSA class and sum MFI at baseline appear to be prognostic. The higher the sum MFI of dnDSA at baseline, the higher the incidence of AMR. Abstract : The authors describe the histologic changes on sequential kidney allograft biopsies following the development of de novo donor‐specific antibody and the specific characteristics of donor‐specific antibodies associated with antibody‐mediated rejection.